Promoting Transparency and Accountability in the Oil and Gas Extractive Industry Sector for Sustainable Development in Bojonegoro Regency - Sholikin, Ahmad; Kresna Martha Sena, Noman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This study aims to identify the challenges in implementing the principles of transparency and accountability in the governance of extractive industries, particularly in the oil and gas sector in Indonesia. Despite efforts toward democratic reforms, fully democratic governance has not yet been achieved. Transparency and accountability aim to establish information openness in revenue management while encouraging public participation for sustainable development. This study develops an analytical framework based on the "transparency continuum," highlighting information openness, citizen actions, and state responses as key elements to enhance change initiatives. Using a qualitative approach, the research analyzes the implementation of transparency and accountability in Bojonegoro Regency, uncovering the complexities and local contexts in supporting sustainable development within the oil and gas sector.